PATHOGENICITY OF Pseudomonas aeruginosa IN RECIPROCAL HYBRIDS OF Clarias gariepinus AND Heterobranchus bidorsalis - OBISESAN, O.M; OLADOSU, G.A.; ADELAKUN, O.D.; AJIBADE, A.O.; ADAH, A.D.; OLOKO, A.B.; BAMIGBOYE, O.F. (Nigerian Journal of Fisheries, 2022)
Farming of hybrids of two African Clariid catfish species, “Heteroclarias” is becoming a focus of attention in many aquatic farms in Nigeria. Pseudomonas sp. is one of the major pathogens responsible for disease in aquaculture. A total of 150 Heteroclarias juveniles were orally inoculated with different concentrations of Pseudomonas aeruginosa ranging from 3 x 101 to 3 x104 CFU/100µl in 4 groups (A to D) replicated thrice, for 14 days with the aim of evaluating its pathogenicity. The control group (E) also with 10 fish in 3 replicates were given normal saline orally. Clinical signs, mortality, histopathology and haematology were observed following experimental infection. Haematological parameters observed were statistically analysed using SPSS 20. Clinical signs observed in group A to C were discolouration, sloughing and patches of haemorrhage on their skin, Frequency of mortality recorded in group A to E were 20%, 10%, 10%, 6.6% and 0% respectively. Histopathological changes observed were vacuolar degeneration of renal tubular epithelium, diffuse hepatocellular vacuolar degeneration, and hyperplasia, fusion of secondary lamellae, with haemorrhage in the gills. Significant difference in haemoglobin concentration parameter was observed, translating to reduction in oxygen carrying capacity of the infected fish. Heteroclarias were susceptible to Pseudomonas aeruginosa, with resultant significant mortality.